2022
DOI: 10.1136/neurintsurg-2022-018749
|View full text |Cite
|
Sign up to set email alerts
|

CLinical Assessment of WEB device in Ruptured aneurYSms (CLARYS): 12-month angiographic results of a multicenter study

Abstract: BackgroundThe CLinical Assessment of WEB device in Ruptured aneurYSms (CLARYS) study has shown that the endovascular treatment of ruptured bifurcation aneurysms with the Woven EndoBridge (WEB) is safe and effective and provides protection against rebleeding at 1 month and 1 year. The 12-month angiographic follow-up is an important endpoint of the study.MethodsThe CLARYS study is a prospective multicenter study conducted in 13 European centers. The study enrolled 60 patients with 60 ruptured aneurysms of the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…In the CLARYS study, 21 12-month anatomic results were slightly different compared with the present series, with a lower rate of complete aneurysm occlusion (41.3%) and higher rates of neck (45.7%) and aneurysm (13.0%) remnants. However, the rate of adequate occlusion was higher (87.0%).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…In the CLARYS study, 21 12-month anatomic results were slightly different compared with the present series, with a lower rate of complete aneurysm occlusion (41.3%) and higher rates of neck (45.7%) and aneurysm (13.0%) remnants. However, the rate of adequate occlusion was higher (87.0%).…”
Section: Discussioncontrasting
confidence: 88%
“…18 In parallel to the technical evolution of the WEB device, its indications progressively enlarged to distal and sidewall aneurysms. [11][12][13] Several multicenter prospective series, including WEB Clinical Assessment of Intrasaccular Aneurysm Therapy (WEBCAST), 3 WEBCAST 2, 5 French Observatory, 6 WEB Intrasaccular Therapy (WEB-IT), 10 and CLARYS, 21 have demonstrated favorable safety and efficacy of EVT with the WEB device; however, these studies were conducted before the introduction of the 17 system.…”
mentioning
confidence: 99%
“…However, only the Woven EndoBridge device has been approved for clinical use in China but not for treating ruptured intracranial aneurysms. A prospective multicenter assessment of the Woven EndoBridge device in ruptured aneurysms conducted by Spelle et al ( 41 ) presented a complete occlusion rate of 41.3% (19/46) at 1 year follow-up. Another study by Youssef et al ( 42 ) revealed that 61.5% of cases achieved complete occlusion in follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…At 1 year, 41.3% of aneurysms were completely occluded (Raymond-Roy Class I; RR I), 45.7% residual neck (RR II), and 13.0% residual aneurysm (RR III) with 13% retreatment rate. 11 While this study did have independent radiographic adjudication, it lacked a randomized comparison treatment group. The World-WideWEB Consortium is an international multicenter cohort including patients with both unruptured and ruptured aneurysms treated with the WEB device.…”
Section: Incorporating New Devices Such As Endosaccular Flow Divertersmentioning
confidence: 99%